(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This study proposes an engineering framework for improving industrial wastewater treatment efficiency while reducing specific energy consumption through rational selection of electrochemical reactor architecture and electrode system design. The work synthesizes electrochemical and transport principles to identify the dominant energy drivers in practical cells, including ohmic losses, non-uniform current distribution, gas holdup, and electrode passivation.